Human Resources in the Digital Order Management Information System (SIMPEL OM) - Cahyono Cahyono; Edi Hamdi; Rhian Indradewa; Ferryal Abadi (Syntax Corporation Indonesia, 2023)
After determining operational goals and targets, Simpel OM then determines a strategy so that the quality of work of employees and Operators becomes competitive and credible. The Simple OM human capital strategy is applied more to developing the skills and direction of each staff's job description, especially those that are closely related to the main strategy in QSPM. QSPM related to HR is recruiting qualified and experienced IT staff as one way to run the Simple OM platform more easily and easily accessed, recruiting and training Field Marketing staff for outreach to material stores, the community and to provide communication and practice. Simple OM application for material shop users, employing quality and targeted human resources, and organizing and creating training that is right on target.